WISE TO USE THE MUSICAL ART OF THE MEDIEVAL ORIENTAL SCIENTISTS - Baltaniyazov Sarsenbay Aitmuratovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article eastern mentioned the idea that eastern scholars treated different illnesses with the help of music. Precisely the author investigated Ibn Sino’s opinions about the role and importance of music in medicine. Besides, there were mentioned the ideas of other nations related to musical treatment.